HUBUNGAN ANTARA EFIKASI DIRI DAN KONSEP DIRI DENGAN PRESTASI BELAJAR DALAM PEMBELAJARAN AKUNTANSI BIAYA PADA MAHASISWA PENDIDIKAN AKUNTANSI UNS - Diana Fitri; Elvia Ivada (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine: (1) the relationship between self-efficacy and academic achievement in cost accounting; (2) the relationship between self-concept and academic achievement in cost accounting; and (3) the simultaneous relationship of self-efficacy and self-concept with academic achievement in cost accounting among Accounting Education students at Universitas Sebelas Maret (UNS). This quantitative survey research involved active students from cohorts 2022–2024 who had completed the cost accounting course (N=250). A sample of 154 students was selected using proportional stratified random sampling. Data were collected via structured questionnaires verified for validity and reliability. Data analysis included descriptive statistics, simple correlation, multiple correlation, and coefficient of determination. Results indicate that self-efficacy and self-concept are positively and significantly related to academic achievement both partially and simultaneously. Integrated enhancement of academic self-concept and self-efficacy serves as a crucial determinant for optimizing cost accounting learning outcomes.